Peran Mediasi Struktur Modal Dan Moderasi Ukuran Perusahaan Pada Likuiditas Terhadap Nilai Perusahaan - Paisal Anwar; Wawan Ichwanudin; Ika Utami Widyaningsih (Tirtayasa Ekonomika, 2025)
This study aims to examine the effect of liquidity on firm value mediated by capital structure and moderated by firm size in food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2016-2023.The study uses a causal research type with a quantitative method by examining comparative causality relationships, using secondary data from the financial statements of each company, both obtained through the IDX website and the official website of each company. Sampling uses a non-probability method on companies listed in the food and beverage sub-sector listed on the IDX in 2016-2023. The research data is panel data analyzed using SPSS and Hayes Process with analysis stages, namely descriptive statistics to conditional process analysis. The results of the hypothesis test show that: 1) liquidity has a negative and significant effect on firm value. 2) liquidity has a negative and significant effect on capital structure. 3) Capital structure has a negative and significant effect on firm value. 4) Capital structure is able to mediate the effect of liquidity on firm value. 5) Firm size is able to moderate the effect of liquidity on firm value.